2013
DOI: 10.1074/jbc.m113.496281
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase 7 Promotes Toll-like Receptor 4-dependent Proinflammatory Gene Expression in Macrophages

Abstract: Background: Histone deacetylase (HDAC) inhibitors reduce LPS-induced inflammatory mediator production from macrophages, but the relevant HDAC targets are unknown. Results: A specific isoform of Hdac7 amplifies expression of LPS-inducible genes via a HIF-1␣-dependent mechanism in macrophages. Conclusion:The class IIa HDAC Hdac7 promotes inflammatory responses in macrophages. Significance: Hdac7 may be a viable target for developing new anti-inflammatory drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 59 publications
7
65
0
Order By: Relevance
“…22 HDAC-7 could promote TLR4-dependent proinflammatory gene expression in macrophages. 15 Accordingly, HDAC inhibitor TSA could specifically inhibit LPSdependent gene expression in inflammatory macrophages 23 or epithelial cells. 24 TSA was also reported to suppress cell proliferation and epithelial-mesenchymal transition through inactivation of the component of LPS/TLR4 signaling pathway, such as phosphatidylinositol-3-kinase (PI3K)/Akt, p38 mitogen-activated protein kinase (MAPK), and extracellular signal-regulated kinase(ERK)1/2 pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 HDAC-7 could promote TLR4-dependent proinflammatory gene expression in macrophages. 15 Accordingly, HDAC inhibitor TSA could specifically inhibit LPSdependent gene expression in inflammatory macrophages 23 or epithelial cells. 24 TSA was also reported to suppress cell proliferation and epithelial-mesenchymal transition through inactivation of the component of LPS/TLR4 signaling pathway, such as phosphatidylinositol-3-kinase (PI3K)/Akt, p38 mitogen-activated protein kinase (MAPK), and extracellular signal-regulated kinase(ERK)1/2 pathways.…”
Section: Discussionmentioning
confidence: 99%
“…15 To test whether LPS/TLR4 promotes the proliferation of lung fibroblasts via HDACs, we determined the effect of LPS/TLR4 on HDAC-4, -5, and -7 expression and activation in lung fibroblasts. We infected lung fibroblasts with TLR4-siRNAlentivirus or treated cells with HDAC inhibitor TSA in the presence or absence of LPS challenge for different time points and assessed the HDAC-4, -5, and -7 mRNA and protein expression by real-time PCR and western blot, respectively.…”
Section: Silencing Of Tlr4 Inhibits Lps-enhanced Proliferation Of Lunmentioning
confidence: 99%
“…Whereas M1 macrophages are pro-inflammatory and have a central role in atherosclerosis development and plaque rupture, M2 macrophages are associated with response to anti-inflammatory reactions, tissue remodeling, fibrosis and atherosclerosis regression 6 . Recent studies demonstrate that among HDACs, HDAC3 and HDAC7 have been identified to play a key role in inflammatory gene expression program and alternative activation of macrophages 79 . However, the role of HDAC9 in these processes in macrophages is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…HDACi are reported to inhibit proinflammatory cytokine secretion via multiple mechanisms, including inhibiting the transcriptional activity of hypoxia-inducible factor 1-alpha (HIF-1␣) (8,11), impairing recruitment of proinflammatory transcription factors to target promoters (12), reducing the stability of mRNAs encoding inflammatory cytokines (13), and upregulating the expression and activity of the transcriptional repressor complex, Mi-2/NuRD (14). Such studies imply that certain HDACs have proinflammatory functions, and indeed this has been reported for a number of HDACs, for example, HDAC4 (15) and HDAC7 (11). As proinflammatory cytokines play important roles in host defense, it is a distinct possibility that HDACi may, in dampening inflammation, also compromise host defense.…”
mentioning
confidence: 99%